2014
DOI: 10.1101/001743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing Microtubule Motors Control Motility, Morphology, and Cargo Segregation During ER-to-Golgi Transport

Abstract: BSTRACTWe recently demonstrated that dynein and kinesin motors drive multiple aspects of endosomal function in mammalian cells. These functions include driving motility, maintaining morphology (notably through providing longitudinal tension to support vesicle fission), and driving cargo sorting. Microtubule motors drive bidirectional motility during traffic between the endoplasmic reticulum (ER) and Golgi. Here, we have examined the role of microtubule motors in transport carrier motility, morphology, and doma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The mammalian light intermediate chains, encoded by two closely related gene products LIC1 and LIC2 (Hughes et al, 1995;Tynan et al, 2000), are involved in several different types of cargo interactions and dynein-based movements, including endosomal and lysosomal transport, ER export, Golgi transport, and axonal vesicle trafficking (Palmer et al, 2009;Horgan et al, 2010;Kong et al, 2013;Tan et al, 2011;Brown et al, 2014;Koushika et al, 2004). The domain structure of the LIC allows it to interact with cargo adaptors while integrated into the dynein holoenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian light intermediate chains, encoded by two closely related gene products LIC1 and LIC2 (Hughes et al, 1995;Tynan et al, 2000), are involved in several different types of cargo interactions and dynein-based movements, including endosomal and lysosomal transport, ER export, Golgi transport, and axonal vesicle trafficking (Palmer et al, 2009;Horgan et al, 2010;Kong et al, 2013;Tan et al, 2011;Brown et al, 2014;Koushika et al, 2004). The domain structure of the LIC allows it to interact with cargo adaptors while integrated into the dynein holoenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…When a non motor chain of kinesin 2 KAP3 is depleted, the anterograde transport ERES -ERGICcis Golgi is not affected, whereas the reverse COPI dependent return of KDEL R marker protein to ER is inhibited [33]. Detailed analysis of movements of COPI coated ts045 VSV G containing vesicles in the cell showed that the depletion of dynein, as expected, leads to dramatically decreased number of moving particles [6]. The effect of depletion of kinesin 1 was unexpected: the number of moving particles was also reduced, but the remaining moving vesicles strongly increased the length of tracks.…”
mentioning
confidence: 59%
“…The effect of depletion of kinesin 1 was unexpected: the number of moving particles was also reduced, but the remaining moving vesicles strongly increased the length of tracks. Depletion of kinesin 2 did not affect the num ber of moving vesicles, but also increased the length of the tracks [6]. From these data it can be concluded that kinesins inhibit dynein dependent anterograde transport from the ER to Golgi, and kinesin 1 is involved in retro grade transport [6].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Kinesin-2 proteins perform an important and conserved function in IFT and flagellar biogenesis of primary and motile cilia (Lechtreck, 2015; Scholey, 2013). Kinesin-2 proteins have also been implicated in bidirectional endoplasmic reticulum (ER) to Golgi transport (Brown et al, 2014; Stauber et al, 2006), endosomal trafficking (Granger et al, 2014), transport in neurons (Hirokawa et al, 2010), cilium-based signaling (Goetz and Anderson, 2010), chromosome segregation (Haraguchi et al, 2006; Miller et al, 2005), and cytokinesis completion (Brown et al, 1999; Fan and Beck, 2004). Here, we report that the two kinesin-2 proteins TbKin2a and TbKin2b in BSF T. brucei function in flagellar biogenesis, but only TbKin2a appears to be crucial for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%